Multi-Pathway Study for Oxaliplatin Resistance Reduction - Tong Ye; Chen Wu; Jintong Na; Xiyu Liu; Yong Huang (Current Issues in Molecular Biology)
Chemotherapy for cancer frequently uses platinum-based medications, including oxaliplatin, carboplatin, and cisplatin; however, due to their high systemic toxicity, lack of selectivity, drug resistance, and other side effects, platinum-based medications have very limited clinical application. As a first-line medication in antitumor therapy, oxaliplatin must be administered to minimize side effects while achieving anticancer objectives. A new CDC7 inhibitor called XL413 has demonstrated promising antitumor therapeutic effects in a variety of malignant tumors and may have anticancer properties. This offers a fresh viewpoint on how to lessen oxaliplatin resistance and, specifically, increase the potency of already prescribed anticancer therapies. In this paper, the current developments in anticancer therapy are discussed, along with the many mechanisms of oxaliplatin’s antitumor effects, clinical treatment challenges, and related approaches. We conducted more research on oxaliplatin resistance that arose during chemotherapy and searched for ways to lessen it in order to enhance its chemotherapeutic performance. Ultimately, we studied how distinct resistance routes relate to one another. Meanwhile, XL413, a novel CDC7 inhibitor, offers a perspective on the possibilities for developing treatment approaches for this innovation point. The search terms “Oxaliplatin, XL413, drug resistance, cancer treatment,” etc., were applied in the X-MOL and PubMed databases for this review’s literature search. Boolean logic was then employed to maximize the search approach. These databases can offer thorough research data and cover a broad range of biological publications. Excluded publications were works of low relevance, duplicates, or those with insufficient information. The mechanism of oxaliplatin’s anticancer effect, oxaliplatin resistance and its amelioration, and the role of XL413 in oxaliplatin treatment were the main topics of the 140 publications that were ultimately included for analysis.